Hubungan Antara Interaksi Teman Sebaya Dengan Kematangan Emosional Peserta Didik Madrasah Tsanawiyah - Andika Ari Saputra (Journal of Contemporary Islamic Education, 2023)
This research aims to determine the relationship between peer interactions and the emotional maturity of junior high school students. This research is a correlation and reveal facto research. The population of this study was all junior high school students, totaling 504 students. A sample of 252 students was determined using proportional stratified random sampling technique. The variable studied is between peer interaction and emotional maturity. The data collection method uses a scale (inventory), the tools are a peer interaction scale and an emotional maturity scale. The validity test was carried out with the help of the SPSS 22 for Windows computer program. Reliability test using Cronbach's alpha technique, obtained p = 0.720 for the peer interaction variable and p = 0.711 for the emotional maturity variable. The analysis technique used is descriptive and inferential statistics with the SPSS 22 for Windows program. The results of the research show that there is a relationship between peer interaction and the emotional maturity of junior high school students of 0.831, the Ts 5% probability figure is 0.000 (p<0.05).